Determinants of residential location choices by slum dwellers in Lagos megacity. (March 2020) - Badmos, Olabisi S.; Callo-Concha, Daniel; Agbola, Babatunde; Rienow, Andreas; Badmos, Biola; Greve, Klaus; Jürgens, Carsten
Abstract: Despite the deplorable condition of slums, it still harbors most of the urban population and may continue to do so, especially in Africa where slum growth is on a par with urban growth. This is the case in Lagos, a megacity reportedly dominated by slum dwellers, with limited knowledge on residential choices of slum dwellers and its contribution to slum population growth. This study, therefore, investigated the movement pattern of slum dwellers, factors influencing the residential choices and reasons for the people to remain in the Lagos slums. Data was collected through questionnaires and focus group discussions in slums in Lagos. The findings show that movement to Lagos was the main cause of population growth in the slums. Furthermore, slums in Lagos serve as a sink and a final destination for slum dwellers. Also, the factors that attract most of the slum dwellers to the slums differ from those that made them wish to remain. The identified factors were based on the socio-demographic characteristics of the respondents, it is therefore important for the Lagos state Government to incorporate them in their slum management policies, especially when relocation of slum dwellers is the only alternative. Highlights: We investigated the factors influencing the residential choices and causes of people to stay/or move from Lagos slums Slums serves as a sink and final destination to slum dwellers in Lagos Factors that brought most of the slum dwellers to the slums differs from the ones that made them stay Socio-demographic characteristics of slum dwellers should be incorporated into slum management policies in Lagos